2008
DOI: 10.1007/s00422-008-0272-7
|View full text |Cite
|
Sign up to set email alerts
|

The response of cortical neurons to in vivo-like input current: theory and experiment

Abstract: The study of several aspects of the collective dynamics of interacting neurons can be highly simplified if one assumes that the statistics of the synaptic input is the same for a large population of similarly behaving neurons (mean field approach). In particular, under such an assumption, it is possible to determine and study all the equilibrium points of the network dynamics when the neuronal response to noisy, in vivo-like, synaptic currents is known. The response function can be computed analytically for si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 151 publications
(273 reference statements)
3
40
0
Order By: Relevance
“…Our results suggest a smoother transition in this non-linear region (Figure 3A), which is in agreement with other in vivo data (Priebe et al, 2004) and in vitro data stimulating the neurons with in vivo like inputs (La Camera et al, 2008), both obtained from neocortical neurons. It is possible that this property is more pronounced in an in vivo setting such as ours with an intense synaptic background activity as compared to in vitro since previous simulation work has suggested that the background level of stochastic synaptic input changes the dynamics of spike firing (Jaeger and Bower, 1999; Gauck and Jaeger, 2000, 2003; Destexhe et al, 2001; Salinas and Sejnowski, 2002; Fellous et al, 2003; Suter and Jaeger, 2004), especially close to the threshold (La Camera et al, 2008). A suitable description of the spike firing statistics should therefore be capable of featuring both a sharp and a smooth threshold in this region.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results suggest a smoother transition in this non-linear region (Figure 3A), which is in agreement with other in vivo data (Priebe et al, 2004) and in vitro data stimulating the neurons with in vivo like inputs (La Camera et al, 2008), both obtained from neocortical neurons. It is possible that this property is more pronounced in an in vivo setting such as ours with an intense synaptic background activity as compared to in vitro since previous simulation work has suggested that the background level of stochastic synaptic input changes the dynamics of spike firing (Jaeger and Bower, 1999; Gauck and Jaeger, 2000, 2003; Destexhe et al, 2001; Salinas and Sejnowski, 2002; Fellous et al, 2003; Suter and Jaeger, 2004), especially close to the threshold (La Camera et al, 2008). A suitable description of the spike firing statistics should therefore be capable of featuring both a sharp and a smooth threshold in this region.…”
Section: Resultssupporting
confidence: 93%
“…The relationship between the input current and the spike firing frequency is frequently reported to be linear (Nowak et al, 2003; Mckay and Turner, 2005; Molineux et al, 2005; Meehan et al, 2010; Zhong et al, 2010). However, as the firing frequency of a neuron approaches zero the linearity inevitably disappears, either by a sharp threshold or by a smoother transition between zero and non-zero firing, also shown theoretically using leaky integrate-and-fire (LIF) neuron models (Fourcaud-Trocme et al, 2003; La Camera et al, 2008). Our results suggest a smoother transition in this non-linear region (Figure 3A), which is in agreement with other in vivo data (Priebe et al, 2004) and in vitro data stimulating the neurons with in vivo like inputs (La Camera et al, 2008), both obtained from neocortical neurons.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A simplified spike-rate model accounting for the patterned electrical activity emerging in populations of cultured neurons was defined and computersimulated to interpret the electrophysiological recordings. We described the firing rate, R(t), of the ensemble of cortical neurons in terms of the single-cell f-I curve and recurrent connectivity La Camera et al, 2008). The model replicates some of the features characterizing the population bursts as transient irregular outbursts in R(t).…”
Section: Methodsmentioning
confidence: 99%
“…1a, respectively) are more or less excitable, respectively. Gain functions have been worked out for several integrate-and-fire (IF) neurons and synaptic transmission models (see for review Burkitt 2006;La Camera et al 2008). Here we use a U(m) derived in (Fusi and Mattia 1999) for a simplified IF neuron model.…”
Section: Mean-field Theory Of Neuronal Network Dynamicsmentioning
confidence: 99%